APPLICATION OF DEVICES FOR SPACE-RESOLVED SPECTROSCOPY ON THE EXAMPLE OF TWO-LAYER PHANTOMS CONTAINING METALLIC NANOPARTICLES - M. N. Kholodtsova; P. V. Grachev; W. C. Blondel; P. V. Zelenkov; A. A. Potapov; I. A. Shcherbakov; V. B. Loschenov (Biomedical Photonics, 2018)
The abilities of the optical probe for fluorescence-guided stereotactic biopsy were investigated by means of a multifiber probe under 532 or 632.8 nm excitation. The set of multilayered phantoms representing a border between normal brain-tissue and a tumor with photosensitizer and gold nanoparticles (spheres or stars) in different concentrations were made to investigate the macroscopic parameters observed during the neurosurgical biopsy sample collection by means of the optical probe. These investigantions will allow to define the border of a brain tumor and control the type of tissue being collected by a stereotactic cannula during surgery. The impact of gold nanospheres and gold nanostars added in different concentrations to the bottom-layer of phantom was analyzed by fluorescence quenching or enhancement due to energy transfer between nanoparticles and fluorescent molecules. The results allow determining the tumor border and to make the biopsy uptake more efficient by observing the character of signal change while penetrating a tumor and while going out of it.